Digital Twin as a Tool for Supporting Logistics Coordination in Distribution Networks - Mariusz Kmiecik (International Journal of Supply Chain Management, 2023)
We all witness changes in supply chains and distribution networks influenced by technological development. One of the trends is Digital Twins and outgoing outsourcing of logistics processes. According to mentioned trends, the following article is aimed to elaborate on the Digital Twin in the wide understanding logistics coordination concept. The research focuses on examining the 4 chosen distribution networks in which logistics service providers collaborate with manufacturers in the area of e-commerce activities. The results from the different simulation models were shown and the perspective of implementation of the Digital Twin was clarified.